Mechanisms controlling the trafficking, localization, and abundance of presynaptic Ca2+ channels - Cunningham, Karen L.; Littleton, J. Troy (Frontiers in Molecular Neuroscience, 2023)
Voltage-gated Ca2+ channels (VGCCs) mediate Ca2+ influx to trigger neurotransmitter release at specialized presynaptic sites termed active zones (AZs). The abundance of VGCCs at AZs regulates neurotransmitter release probability (Pr), a key presynaptic determinant of synaptic strength. Given this functional significance, defining the processes that cooperate to establish AZ VGCC abundance is critical for understanding how these mechanisms set synaptic strength and how they might be regulated to control presynaptic plasticity. VGCC abundance at AZs involves multiple steps, including channel biosynthesis (transcription, translation, and trafficking through the endomembrane system), forward axonal trafficking and delivery to synaptic terminals, incorporation and retention at presynaptic sites, and protein recycling. Here we discuss mechanisms that control VGCC abundance at synapses, highlighting findings from invertebrate and vertebrate models.